Pengembangan Sistem Informasi E-Complaint Management (Studi Kasus : Batching Plant Produksi Beton P.T. Holcim Indonesia Regional Jawa Timur) - Yhouga Beta Evantio; Retno Indah Rokhmawati; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Batching Plant PT. Holcim is part of PT. Holcim which handle the distribution and production of PT. Holcim's products, such as concrete, ready made cement concentrate, and building construction services. Customers can order the products and services at Batching Plant PT. Holcim without having to go to headquarters of P.T Holcim. From each service provided by Batching Plant PT. Holcim, customers can report complaints due to errors from service process to Batch Plant PT. Holcim directly. The problem is the process of recording complaints are still done manually so it's difficult for sales accommodate complaint data. In addition, sales are also difficult to tell the leader of the job complaint must be done immediately. Based on the problem that CRM applications need to be able to assist sales and leaders in performing complaint reporting processes with CRM operational application types. The CRM application needed to record the complaint automatically. In addition, CRM application required to help sales inform to the leader that new complaint must be done immediately. Later on, the system has features such as make new complaint, make notification to the leader, and managing complaint data. In its development the method used to develop the system using codeigniter framework. Then the system will be tested using Base Path Testing, User Acceptance Testing and Utility Testing for success level in fulfilling user's need.